Masked tachycardia. A predictor of adverse outcome in hypertension. Issue 3 (March 2017) - Palatini, Paolo; Reboldi, Gianpaolo; Beilin, Lawrence J.; Casiglia, Edoardo; Eguchi, Kazuo; Imai, Yutaka; Kario, Kazuomi; Ohkubo, Takayoshi; Pierdomenico, Sante D.; Schwartz, Joseph E.; Wing, Lindon; Verdecchia, Paolo
Abstract : Objective: The relative role of office heart rate (HR) and ambulatory HR for predicting major adverse cardiovascular events (MACEs) and mortality is not well known. Aim of this study was to investigate the association of white-coat tachycardia and masked tachycardia with MACE and mortality in hypertensive patients. Methods: We performed 24-h ambulatory blood pressure and HR monitoring in 7602 hypertensive patients (4165 men) aged 52 ± 16 years enrolled in six prospective studies in Italy, Japan, and Australia. Participants were divided into four groups: normal office and normal night-time HRs ( N  = 5238), white-coat tachycardia ( N  = 998), masked tachycardia ( N  = 796), and sustained tachycardia ( N  = 570). Median follow-up was 5.0 years. Results: In age-and-sex-adjusted Cox model, using the normal HRs group as a reference, white-coat tachycardia was not a significant predictor of excess MACEs or all-cause death. In contrast, both masked tachycardia [hazard ratio, 95% confidence interval (CI); 1.40, 1.11–1.77] and sustained tachycardia (1.86, 1.44–2.40) were associated with risk of excess MACE. In addition, masked tachycardia (hazard ratio, 95% CI; 1.62, 1.14–2.29) but not sustained tachycardia (1.35, 0.83–2.19) was a significant predictor of excess mortality. These relationships held true in multivariable parsimonious Cox models including major risk factors. In these models, masked tachycardia remained an independent predictor of excess MACE (hazard ratio, 95% CI; 1.34, 1.06–1.71) and all-cause mortality (1.68, 1.18–2.41). Conclusion: The current study confirms that measurement of HR adds to the risk stratification for MACE and mortality and shows that an elevated night-time HR confers an increased mortality risk to hypertensive patients who have normal office HR.